A Study on Work Life Balance Amongst Nurses With Special Reference To West Delhi (Trinity Journal of Management, IT & Media (TJMITM), 2015)
Work- life balance is the matter of concern in 21st century. It is really  tough to strike a balance between family and work in this competitive  era. One has to understand that work life and personal life are the two  sides of the same coin. It is very difficult for an individual to fulfill the  demands of both professional as well as personal life. Now- a- days an  individual may find himself working continuously from 7 a.m. to 11 p.m.,  even answering email and calls during mealtime. Work easily invades  our personal lives because of the simple fact that money dominates the  modern life. When there’s no balance in personal and professional life it  leads to loss in productivity and too often it affects the individual’s health. This research paper is an attempt to study the work life balance issues  with reference to nurses working in west Delhi area as well as the factors  that determine work life balance.
Keywords: Work- life balance; WLB Problems; Impact of WLB